Energy Requirement of Patients Undergoing Hemodialysis: A Cross-Sectional Study in Multiple Centers. (21st March 2020) - Wu, Pei-Yu; Chen, Yu-Tong; Wong, Te-Chih; Chen, Hsi-Hsien; Chen, Tzen-Wen; Chen, Tso-Hsiao; Hsu, Yung-Ho; Peng, Sheng-Jeng; Kuo, Ko-Lin; Hung, Szu-Chun; Yang, Shwu-Huey
Abstract : Background . Energy requirements must be estimated before nutritional care can be provided for patients undergoing hemodialysis (HD). However, the recommended caloric intake for patients has not been conclusively determined because of insufficiently large sample sizes. Method . This cross-sectional observational study recruited patients undergoing long-term HD from multiple centers as well as people in the general population without chronic kidney disease. People from both groups were matched by sex and age. Resting energy expenditure (REE) was estimated using an indirect calorimeter. Two commonly used equations for estimating REE and daily energy requirement recommended by the National Kidney Foundation's Kidney Disease Outcomes Quality Initiative (K/DOQI) were chosen. Results . This study had 154 HD patients and 33 matched HD–control group pairs. Age ( r = −0.36, p < 0.01 ) and dry body weight after dialysis ( r = 0.54, p < 0.01 ) were identified as the primary factors affecting total energy expenditure (TEE). When compared with measured energy expenditure, the recommended equations for evaluating energy expenditure, namely, the Harris–Benedict, Schoenfeld, and K/DOQI-recommended equations, were biased and imprecise for HD patients of different sexes and body sizes. Moreover, the TEEs of HD patients (26.8 ± 5.5 kcal/kg/day) and the matched control patients (25.3 ± 5.1 kcal/kg/day) did not significantly differ. Conclusions . Age and dry body weight are the main factors affecting the energy expenditure of HD patients. Furthermore, predicting the energy expenditure of HD patients by measuring the energy expenditure of their sedentary counterparts in the general population with the same sex, age range, and weight may yield better results than using traditional equations for predicting TEE. In East Asian populations, the TEE values were 32 and 30 kcal/kg dry weight for those aged <65 and ≥65 years, respectively. Future prospective cohort studies with larger sample sizes are needed.